Thursday

October 23, 2014

October 23, 2014

Posted by **ROCKY** on Tuesday, August 2, 2011 at 8:14pm.

- intermediate algebra -
**Damon**, Tuesday, August 2, 2011 at 8:18pm36 = x^2 -14 x + 49

x^2 -14 x + 13 = 0

(x-13)(x-1) = 0

x = 13 or x = 1

**Answer this Question**

**Related Questions**

intermediate algebra - given the quadratic function f(x)=9x^2+36x+36, finda ...

Algebra - Use the intermediate theorem to show that the polynomial function ...

algebra - solve the following equation by clearing fractions show all work want ...

algebra - Suppose that f(x)is a polynomial with integer coefficients, such thatf...

ALGEBRA - Suppose that f(x)is a polynomial with integer coefficients, such thatf...

College Algebra - 1. Use the Intermediate Value Theorem to show that the ...

intermediate value thorem - Use intermediate value theorem to show that the ...

Calculus - Let f be a twice-differentiable function such that f(2)=5 and f(5)=2...

Maths - find the equation of the perpendicular bisector of the line joining P(2...

calculus - Use the intermediate value theorm to show that the polynomial ...